Expert System Detection of Cataract Using Production Rules - Priska Ambarsari (Institute of Computer Science (IOCS), 2020)
Eyes are one of the five very important senses. If the eye is disturbed, it will inhibit human activities. Eye detection as early as possible will help the public to know the disease. However, patients often cannot consult an ophthalmologist because the doctor cannot be found. The cataract detection expert system was built to help the public and eye doctors to detect cataracts at an early stage. Cataract is one of the eye diseases that causes blindness. Cataracts have symptoms of blurred vision, sensitivity to light, difficulty seeing at night and other symptoms. These symptoms were processed using the IF-THEN production rule and reasoning using conjunctive syllogisms and ponent mode to determine the diagnosis of the type of cataract suffered by the patient. This expert system is able to predict cataract disease accurately. Based on Azwar's criteria and testing by ophthalmologists as experts and 30 users, it shows that the system built tends to be moderate.